Prenatal Tdap immunization and risk of maternal and newborn adverse events. Issue 33 (24th July 2017) - Layton, J. Bradley; Butler, Anne M.; Li, Dongmei; Boggess, Kim A.; Weber, David J.; McGrath, Leah J.; Becker-Dreps, Sylvia
Abstract: Many countries recommend combined tetanus toxoid, reduced diphtheria toxoid and acellular pertussis immunization (Tdap) during pregnancy to stimulate transplacental transmission of pertussis antibodies to newborns. The immune system can be altered during pregnancy, potentially resulting in differing immunization risks in pregnant women. The safety of widespread Tdap immunization during pregnancy needs to be established. Our objective was to assess whether prenatal Tdap immunization was associated with adverse birth outcomes, and to evaluate the effect of timing of Tdap administration on these outcomes. We identified pregnancies at delivery in a large insurance claims database (2010–2014). Tdap immunization was categorized as optimal prenatal (27 + weeks), early prenatal (<27 weeks), postpartum (≤7 days post-delivery), or none. Medical claims were searched to identify maternal adverse immunization reactions (e.g. anaphylaxis, fever, Guillian-Barre syndrome [GBS]), adverse birth outcomes (e.g. preeclampsia/eclampsia, premature rupture or membranes, chorioamnionitis) and newborn outcomes (e.g. respiratory distress, pulmonary hypertension, neonatal jaundice). Women with optimal or early prenatal Tdap were compared to those not immunized in pregnancy, using propensity score-weighted log-binomial regression and Cox proportional hazards models to estimate risk ratios (RR) and hazard ratios (HR). We identified 1, 079, 034 deliveries and 677, 075 linked newborns; 11.5% were immunized optimally and 2.3% immunized early. There were 1 case of post-immunization anaphylaxis, and 12 cases of maternal encephalopathy (all post- delivery); there were no cases of GBS. Optimally-timed immunization was associated with small increased relative risks of: chorioamnionitis [RR = 1.11, (95% CI: 1.07–1.15), overall risk = 2.8%], and postpartum hemorrhage [RR = 1.23 (95% DI: 1.18–1.28), overall risk = 2.4%]; however, these relative increases corresponded to low absolute risk increases. Tdap was not associated with increased risk of any adverse newborn outcome. Overall, prenatal Tdap immunization was not associated with newborn adverse events, but potential associations with chorioamnionitis consistent with one previous study and postpartum hemorrhage require further investigation.